化简:cos2x/(1-sin2x)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 10:45:32
化简:cos2x/(1-sin2x)化简:cos2x/(1-sin2x)化简:cos2x/(1-sin2x)原式=(cos²x-sin²x)/(cos²x-2·sinx·
化简:cos2x/(1-sin2x)
化简:cos2x/(1-sin2x)
化简:cos2x/(1-sin2x)
原式=(cos²x-sin²x)/(cos²x-2·sinx·cosx+sin²x)
=[(cosx+sinx)(cosx-sinx)]/(cosx-sinx)²
=(cosx+sinx)/(cosx-sinx)
=√2cos(x-45°)/√2cos(x+45°)
=cos(x-45°)/cos(x+45°)
化简:cos2x/(1-sin2x)
化简 (1+sin2x-cos2x)/(1+sin2x+cos2x)
化简(cos2x-sin2x)/(1-cos2x)(1-tan2x)
(1+ sin2x)/(1+ cos2x+ sin2x)化简
化简(1+sin2x)/(1+sin2x+cos2x)
化简[1+SIN2X-COS2X]/[1+SIN2X+COS2X]的结果
化简(1+cos2x/sin2x)乘以(1+cosx/cosx)
sin2x/(1-cos2x)-(1/tanx) 化简
化简 (sin2x)/(1+cos2x)*(cosx)/(1+cosx)
sin2x+cos2x+1/1+tanx 化简
化简:(sinx+sin2x)/(1+sinx+cos2x)
化简:(sinx+sin2x)/(1+cosx+cos2x)
化简sin2x+cos2x
sin2x·cos2x化简
sin2x×cos2x/2,化简.
化简cos2x*sin2x
1-cos2x+sin2x=
(1+sin2x-cos2x)/(1+sin2x+cosx)